Comparison of the diagnostic performance of the 2017 and 2018 versions of LI-RADS for hepatocellular carcinoma on gadoxetic acid enhanced MRI. Issue 4 (April 2020) - Ko, A.; Park, H.J.; Lee, E.S.; Park, S.B.; Kim, Y.K.; Choi, S.-Y.; Ahn, S.
Abstract : AIM: To compare the diagnostic performance of the 2017 (v2017) and 2018 versions (v2018) of the Liver Imaging-Reporting and Data System (LI-RADS) for hepatocellular carcinoma (HCC) using gadoxetic acid-enhanced magnetic resonance imaging (Gd-EOB-MRI) and to evaluate the effect in v2018. MATERIALS AND METHODS: Treatment-naive patients at high-risk for HCC who underwent Gd-EOB-MRI were included. The LI-RADS categories were assigned according to v2017 and v2018. The diagnostic performances were compared between v2017 and v2018 according to the size and combination of imaging features. RESULTS: A total of 117 patients with 137 observations were identified, including 89 HCCs; 76.2% (64/84) of observations with threshold growth were re-classified as subthreshold growth when using v2018 instead of v2017. The final categories changed in nine (14%) cases. For the combination of LR-5/LR-5V, there were no significant differences in sensitivity and specificity between the two versions (sensitivity, 64% versus 58.4%; specificity, 87.5% versus 85.4%; all p> 0.05). For the combination of LR-4 and LR-5/5V, the diagnostic performance of v2018 was inferior to that of v2017 when considering only major features (accuracy, 86.1% versus 80.3%, respectively; p= 0.013), particularly in observations measuring 10–20 mm, but was comparable after adding the ancillary features (accuracy, 86.9% versus 86.1%, respectively; p= 1.00). CONCLUSION: In LI-RADS v2018, although a considerable number of observations re-classified subthreshold growth, changes in the assigned categories were insignificant; overall diagnostic performance was comparable to that of v2017, but v2018 might emphasise the value of ancillary features in combination with major features for determining the probability of HCC. Highlights: Overall, v2018 LI-RADS showed comparable diagnostic performance to v2017 LI-RADS. For 10–19 mm LR-4/5/5V, v2018 had inferior diagnostic performance when considering major features. However, with addition of ancillary features, v2018 was comparable to v2017 LI-RADS. Majority of threshold growth downgraded when applying v2018, there was no significant categorical change.